Gamifikasi Sistem Kerja dan Siasat Pengemudi Gojek - Devita Aditya Wicaksono (School of Communication Science and Media Business, 2020)
This study aims to identify how gamification is in the work system of Gojek and how its drivers handle it. This study was conducted through observations and interviews with Gojek drivers operating in Yogyakarta. Based on the concept of sharing economy and gamification, this study revealed that the gamification work system blurs the boundaries between working and playing. A driver's job is not just taking passengers, delivering goods or food. However, it is like playing a